Heightened intensity: Reflecting on player experiences in Wayfinder Live. (February 2019) - Innocent, Troy; Leorke, Dale
Location-based games use smartphones and other location-aware devices to incorporate their players' actions in everyday, physical spaces – the streets and public spaces of the city – into the virtual world of the game. Scholars and designers of these games often claim that they reconfigure their players' relationship with the people and environment around them. They argue these games either engage and immerse players more deeply in the spaces of the game or distance and detach them from the physical environment through the screen interface. To date, however, relatively few detailed empirical studies of these games have been undertaken to test out and critique these claims. This article presents a study of the 2017 iteration of the location-based augmented reality game Wayfinder Live, in which players use their phones to search for and scan urban codes hidden across Melbourne's laneways, alleys, and public spaces. Players of the game were interviewed and invited to reflect on their experience. This article relates these experiences to the design and development of the game, particularly to five play design principles that characterize its approach to haptic play in urban space. We begin by outlining these principles and the motivations behind them. Then, drawing on an analysis of the player interviews, we evaluate the impact of the game on their perception of the city.